Stillbirth and associated factors among women delivered at Dore-Bafano Primary Hospital, Southern Ethiopia, 2023. A facility based cross sectional study: Original Article - Ermiyas, Samrawit; Yigzaw, Tsegedingel; Assefa, Tesfahun; Kebede, Seyoum; Bedane, Sisay; Tefera, Kebede (Pharma Multidisciplinary Research Journal, 2024)
Background: Over 2 million babies (1 every 16 seconds) are stillborn each year, of which 84% are in low- and middle-income countries. The global incidence of stillbirth ranges from 3.4-36/1000 total births in high-income countries and in the Sub-Saharan and Asia regions. In Ethiopia, despite the governmental and non-governmental efforts to reduce the rate of stillbirth, prevention of stillbirth has remained largely unaddressed. This research aims at narrowing the gap on understanding the magnitude and possible factors of stillbirth.Objectives: To assess the magnitude of stillbirth and associated factors among women who gave birth at Dore-bafana Primary Hospital 2023.Methods: Facility based cross-sectional study was conducted by reviewing medical records of 518 randomly selected births at Dore-bafano Primary Hospital from May 3 to 18, 2023. The data were extracted using a structured checklist by trained data retrievers and checked for its completeness, edited, cleaned and entered into Epi data version 4.7 and exported to SPSS version 29. Bivariable and multivariable binary logistic regression analysis were done to identify associated factors of stillbirth. Associations were measured using both crude and adjusted odds ratios. Finally p-value < 0.05 together with 95% confidence interval were used to determine statistical significance.Results: The prevalence of stillbirth was 3.38% (95% CI: 2%-5.4%) or 33.8 cases/1000 live births within the sample. Several factors were identified as independently associated with stillbirth, including gestational age less than 37 weeks [AOR=0.024 (95% CI: 0.002-0.37)], obstructed labour [AOR= 30.26 (95% CI: 1.14-804.20)], duration of labour exceeding 18 hours [AOR=17 (95% CI: 1.23-253.35)] and congenital anomalies [AOR=19 (95% CI: 1.33-295.02)].Conclusions: The prevalence of stillbirth in this study was high as compared to the global as well as the national stillbirth rate. Factors such as gestational age less than 37 weeks, obstructed labor, duration of labor exceeding 18 hours and congenital anomalies were found to be independently associated with stillbirth. Therefore, it is crucial for healthcare providers at Dore-bafano Primary Hospital to prioritize early detection and management of these risk factors to reduce the occurrence of stillbirths.